Comparative assessment of performances of different oxygen carriers in a chemical looping combustion coupled intensified reforming process through simulation study. (20th July 2020) - Alam, Shadab; Kumar, J. Pradeep; Rani, K. Yamuna; Sumana, C.
Abstract: The present study is focused towards investigating the roles of different oxygen carriers (OCs) in a self-sustained integrated process of chemical looping combustion (CLC) with sorption enhanced steam methane reforming (SESMR) through detailed thermodynamic analysis. This study reports individual steady state plant wide models that are developed and optimized for four different oxygen carriers (Co-, Cu-, Mn- and Fe-based) for the first time. Further, the optimal performances of these schemes with different OCs are compared with that of previously reported Ni based OCs. Simulation results revealed that all these OCs exhibited nearly same energy efficiency ( ɳ ) of ∼60%, except Cu-based OCs that resulted in reduced ɳ of 52.74%. From the overall comparative assessment in terms of methane conversion, H2 purity and yield, CO2 captured, energy efficiency, cost, availability and eco-friendliness, Fe-based OCs are found to be the most suitable ones for CLC-SESMR scheme. Further, exergy analysis has been performed for the optimum Fe-based scheme that resulted in an overall exergetic efficiency of 58.88%. Highlights: Studied the role of metal oxides on CLC coupled Sorption Enhanced Reforming process. Developed and optimized self-sustained schemes with five oxygen carrier (OCs). Ni-based OCs resulted in highest energy efficiency of 61.54% with 96.44% CO2 capture. Fe- and Mn- based OCs resulted in highest H2 purity of 99% with CO2 capture > 97%. Best performance achieved with Fe-based OC including cost and toxicity parameters.